Implementation of the Project Based Learning (Pjbl) Model in Improving Science Learning Outcomes for Grade IV Elementary School Students - Yori Marwinda; Imran; Zainal (al-Afkar, Journal For Islamic Studies, 2026)
This research aims to improve student learning outcomes in Natural and Social Sciences (IPAS) subjects through the application of the Project Based Learning (PjBL) learning model. This research is a Class Action Research (PTK) which is carried out in two cycles. Each cycle consists of four stages, namely planning, implementation of actions, observation, and reflection. The subject of the study is grade IV students of SD Negeri 029/VII Lubuk Sayak (adjust the number of students). Data collection techniques use learning outcome tests, observation sheets of teacher and student activities, and documentation. Data were analyzed descriptively, quantitatively, and qualitatively. The results of the study show that the application of the Project Based Learning model can improve student learning outcomes. In cycle I the percentage of student learning completeness reached (data content), then increased in cycle II to (data content). In addition, student learning activities have also increased because students are more active in group discussions, project completion, and presentation of work results. Thus, the Project Based Learning model has proven to be effective in improving the learning outcomes of social studies for grade IV elementary school students.